An eye-tracking and visual analogue scale attractiveness evaluation of black space between the maxillary central incisors - AL-LAHHAM,Ahmad (2021)
ABSTRACT Objective: To study the influence of black space between the maxillary central incisors on the aesthetic visual perception of the face, via eye-tracking and visual analogue scale (VAS). Methods: Black space between the central incisors was created, for both sexes, as follows: control, 1-mm black space, 2-mm black space and 3-mm black space. Ninety raters participated in this study, divided into three groups: 30 laypeople, 30 nonorthodontists, and 30 orthodontists. After the visual calibration of each observer, eight photographs were presented in the Ogama® software concomitant with the use of the hardware The Eye Tribe®. Ogama generated information depending on the eye-tracking of each rater, regarding the time until the first fixation, time of fixation, heatmap, scanpath, and total time of fixation, to evaluate the areas deemed to be of interest according to the raters. Later on, the VAS was used, where each rater evaluated the images in an album on a scale of zero to 10 points. Results: The eyes and mouth were the areas more often noticed by the raters according to the heatmaps, while no significant difference was observed in time until the first fixation between the three groups of raters (p> 0.05). However, regarding the time of fixation on the mouth, a significant difference was observed (p< 0.05) when comparing the three groups. Conclusion: Black space has a negative effect on the aesthetic perception of the face. The amount of attention on the mouth is correspondent to the size of the black space.